1977
DOI: 10.1128/aac.12.6.748
|View full text |Cite
|
Sign up to set email alerts
|

Methadone: Antimicrobial Activity and Interaction with Antibiotics

Abstract: We studied the effect of methadone, alone and in combination with antimicrobial agents, on two strains each of Staphylococcus aureus, Pseudomonas aeruginosa , and Serratia marcescens isolated from blood streams of parenteral drug abusers with bacterial endocarditis. Methadone has its own antibacterial effect, although at supraphysiological concentrations, and is even synergistic with antimicrobial agents against some organisms. Thus, methadone does not interfere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…While the speci c effects of these compounds require further investigation, some, like n-hexadecanoic acid and 5-eicosene, have shown potential antioxidant activity (Iqbal & Bhanger, 2006;Kubo et al, 1994). Additionally, 3-phenylthiane, Soxide has demonstrated anti-in ammatory properties in preclinical studies (Chen et al, 2010), and methadone N-oxide exhibits potential antimicrobial activity against speci c bacteria (Sheagren et al, 1977). Notably, compounds like 5-methyl-2-phenylindolizine and (1-ethylbuta-1,3-dienyl)benzene have shown interactions with the nervous system, warranting further investigation into their speci c effects (Li et al, 2007;Yagi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While the speci c effects of these compounds require further investigation, some, like n-hexadecanoic acid and 5-eicosene, have shown potential antioxidant activity (Iqbal & Bhanger, 2006;Kubo et al, 1994). Additionally, 3-phenylthiane, Soxide has demonstrated anti-in ammatory properties in preclinical studies (Chen et al, 2010), and methadone N-oxide exhibits potential antimicrobial activity against speci c bacteria (Sheagren et al, 1977). Notably, compounds like 5-methyl-2-phenylindolizine and (1-ethylbuta-1,3-dienyl)benzene have shown interactions with the nervous system, warranting further investigation into their speci c effects (Li et al, 2007;Yagi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Together with carbamazepine, it caused toxic effects in intestinal epithelial cells in vitro and inhibited the growth of several species of bacteria representing a healthy digestive system in children up to 9 years of age (such as Ruminococcus gnavus, Clostridium ramosum, and Roseburia intestinalis) and patients with drug-resistant epilepsy (including "anti-epileptic" Parabacteroides species), while the growth of Staphylococcus caprae, Dorea longicatena, E. coli, and Klebsiella aerogenes growth was enhanced (Ilhan et al, 2022). Tramadol has strong in vitro bactericidal activity against E. coli and S. epidermidis and weak antimicrobial activity against S. aureus and P. aeruginosa (Tamanai-Shacoori et al, 2007), and methadone against S. aureus, P. aeruginosa and S. marcescens (Sheagren et al, 1977). Tramadol administered at concentrations of 12.5 and 25 mg/ml to BALB mice infected with Staphylococcus aureus and Pseudomonas aeruginosa induced a reduction in wound diameter (by inflammation induction and phagocytic activity) caused by S. aureus (Farzam et al, 2018).…”
Section: Analgesics and Anticonvulsantsmentioning
confidence: 99%
“…The results showed that methadone has a bigger antibacterial effect against Staphylococcus aureus than against the two other Gram-negative organisms tested, but only at supraphysiological concentrations. Moreover, it has a partial or total synergistic effect with other antimicrobial agents like nafcillin or gentamicin [16].…”
Section: Opioidsmentioning
confidence: 99%